The prophet ebook - Stevens, Amanda (Graveyard Queen, 2012)
My name is Amelia Gray. I am the Graveyard Queen, a cemetery restorer who sees ghosts. My father passed down four rules to keep me safe and I've broken every last one. A door has opened and evil wants me back. In order to protect myself, I've vowed to return to those rules. But the ghost of a murdered cop needs my help to find his killer. The clues lead me to the dark side of Charleston--where witchcraft, root doctors and black magic still flourish--and back to John Devlin, a haunted police detective I should only love from afar. Now I'm faced with a terrible choice: follow the rules or follow my heart.